Conventional and drug‑eluting bead transarterial chemoembolization in patients with inoperable intrahepatic cholangiocarcinoma: a meta‑analysis - Su-Rong Pan; Xue-Wen Wo; Hong-Fang Zhu; Feng-Fei Xia (Videosurgery and Other Miniinvasive Techniques)
Introduction: In patients with inoperable intrahepatic cholangiocarcinoma (ICC), both conventional transarterial chemoembolization (cTACE) and drug-eluting bead TACE (DEB-TACE) can be employed as therapeutic interventions. However, the relative advantages of these strategies remain to be clarified.